Estimation Method for Disaster Immunity in a Flood Disaster - Nakano, Ryo; Oshikawa, Hideo (Lowland Technology International, 2024)
In this study, disaster immunity—which in a broad sense means disaster prevention capability—was evaluated in cities in Saga Prefecture, Japan in regard to flood disasters because most of the prefecture is a lowland and is considered to be a high-risk disaster-prone area. A positive correlation was identified between the ratio of flood control costs and normal annual precipitation, demonstrating a greater degree of disaster immunity in high-rainfall areas compared with low-rainfall areas; therefore, the ratio of flood control costs to expenses for each local government to date was considered to represent the “current” disaster immunity. Literally “immunity” for precipitation was evaluated. In addition, “future” disaster immunity in consideration of the social and natural environmental changes, including the impacts of climate change, was estimated based on the ratio of flood control costs. As a result, cities in Saga Prefecture are considered to have relatively higher current and future disaster immunity compared with cities in other prefectures. In addition, estimations of current and future disaster immunity have become possible for flood disasters, and the evaluation method can easily be improved in consideration of other components and expanded for types of disasters such as landslide disasters.